Ultra-thin V2O5 nanosheet based humidity sensor, photodetector and its enhanced field emission properties - Pawar, Mahendra S.; Bankar, Prashant K.; More, Mahendra A.; Late, Dattatray J. (RSC Advances, 2015)
We report the synthesis of V2O5 nanosheets by a simple hydrothermal method. The as synthesized V2O5 nanosheets were characterized by Raman spectroscopy, Field Emission Scanning Electron Microscopy (FESEM), Transmission Electron Microscopy (TEM) and UV-Vis spectroscopy. The humidity sensing behaviors were investigated in the range of 11-97% relative humidity (RH) at room temperature. The maximum sensitivity of 45.3%, response time of similar to 4 min and recovery time of similar to 5 min were observed for the V2O5 nanosheet based sensor. We also demonstrated the V2O5 nanosheets as an ultra-violet photodetector with a sensing response time of similar to 65 s and recovery time of similar to 75 s with a maximum photoresponsivity of similar to 6.2%. Further, we have also carried out field emission (FE) investigations of V2O5 nanosheets under a planar ``Diode'' assembly in an ultrahigh vacuum (UHV) chamber at a base pressure of similar to 1 x 10(-8) mbar. The turn on fields required to draw field emission current densities of 1 mu A cm(-2) and 10 mu A cm(-2) are found to be 1.15 V mu m(-1) and 1.72 V mu m(-1), respectively. We achieved a maximum field emission current density of 1.532 mA cm(-2) at an applied electric field of 3.2 V mu m(-1). The field enhancement factors calculated from the slope of the Fowler-Nordheim (F-N) plot are found to be 8530 and 3530 at low field and high field regions, respectively. Our results open up several avenues towards the successful utilization of V2O5 nanosheets and other metal oxide nanosheets for various nanoelectronics device applications including sensors, photodetector and flat panel displays.

Vapour-liquid-solid growth of one-dimensional In2Se3 nanostructures and their promising field emission behaviour - Suryawanshi, Sachin R.; Bankar, Prashant K.; More, Mahendra A.; Late, Dattatray J. (RSC Advances, 2015)
Single crystalline ultra long In2Se3 nanowires have been grown by employing a single step facile thermal evaporation route under optimized conditions on Au/Si wafers, and morphology dependent field emission investigations on the In2Se3 nanostructure at the base pressure -1 x 10(-8) mbar are explored. In addition, structural and morphological analysis of as-synthesized In2Se3 nanostructures has been carried out using XRD, SEM and TEM. A plausible explanation of the vapor-solid-liquid (VLS) growth mechanism based on the experimental results and reported literature has been presented. Furthermore, field emission measurements demonstrate remarkably enhanced emission behaviour, which is explained on the basis of the field enhancement factor and aspect ratio of the nanostructures. The synthesized In25e3 nanowire emitter delivers a very high current density of -1.2 mA cm(-2) at an applied electric field of -6.33 cm(-1). The present results demonstrate In2Se3 as an important candidate for potential applications in nano/micro-electronic devices.

Spatially branched CdS-Bi2S3 heteroarchitecture: single step hydrothermal synthesis approach with enhanced field emission performance and highly responsive broadband photodetection - Bankar, Prashant K.; Pawar, Mahendra S.; Pawbake, Amit S.; Warule, Sambhaji S.; Late, Dattatray J.; More, Mahendra A. (RSC Advances, 2016)
This report explores the controlled hierarchical synthesis of CdS nanostructure branches on Bi2S3 nanorod cores via a facile single step hydrothermal route. Morphological and structural studies reveal the formation of CdS-Bi2S3 heteroarchitecture with excellent stoichiometry between the constituent elements. The growth of CdS over Bi2S3 strongly depends on optimization of the reaction conditions, especially low PVP concentration. Furthermore, the as-synthesized CdS-Bi2S3 heteroarchitecture demonstrates multifunctionality in field emission and photoresponse. Interestingly, the CdS-Bi2S3 heteroarchitecture shows enhanced field emission properties such as low turn-on field (similar to 1.8 V mu m(-1) for 10 mu A cm(2)), high emission current density and better current stability in comparison to Bi2S3 and other nanostructures. The as-synthesized CdS-Bi2S3 heteroarchitecture exhibits considerable response and recovery times, similar to 207 ms and 315 ms, respectively in comparison to bare Bi2S3 nanostructures (similar to 655 ms and 678 ms). The present results demonstrate CdS-Bi2S3 heteroarchitecture as a potential candidate for future optoelectronic device applications.

Enhanced field emission performance of MoO3 nanorods and MoO3-rGO nanocomposite - Bankar, Prashant K.; Khandare, Lina N.; Late, Dattatray J.; More, Mahendra A. (ChemistrySelect, 2017)
The graphene and semiconducting hybrid based nanostructures have emerged as a new class of multifunctional materials with improved performance in comparison to the pristine semiconductors. Here, as-synthesized MoO3-reduced graphene oxide (rGO) nanocomposite emitter exhibits enhanced field emission (FE) behavior as compared to the pristine 1D MoO3 nanorods. The hydrothermally synthesized 1D MoO3 nanorods (1D) are grafted on the rGO sheet (2D) using a simple room temperature sonochemical method. The morphological and structural analysis confirms the attachment of MoO3 nanorods with rGO and the improved conductivity of the sample indicates a strong electronic interaction between them. Furthermore, the FE studies of as-synthesized MoO3 nanorods and MoO3-rGO nanocomposite emitters, carried out at a base pressure -1 x 10(-8) mbar, reveals the values of turn on field (required to draw an emission current density of 1 mu A/cm(2)) as 1.6 and 1.4 V/mu m, respectively. Interestingly, the maximum emission current density of 2810 mA/cm(2) is achieved at a lower applied field of 2.7 V/mu m from the MoO3-rGO nanocomposite emitter. The enhancement in FE performance of MoO3-rGO nanocomposite is attributed to the improved electrical conductivity, mechanical properties and higher concentration of protruding edges (emission sites). This observation can be extended to other graphene-based 1D inorganic hybrid semiconductor nanocomposites, which can provide a valuable opportunity to explore novel hybrid materials for vacuum nano-electronic devices.

Enhanced field emission performance of NiMoO4 nanosheets by tuning the phase - Bankar, Prashant K.; Ratha, Satyajit; More, Mahendra A.; Late, Dattatray J.; Rout, Chandra Sekhar (Applied Surface Science, 2017)
In this paper we report, large scale synthesis of a and beta-NiMoO4 by a facile hydrothermal method and we observed that urea plays important role on the growth of beta-NiMoO4 nanosheets. We have also carried out field emission (FE) investigations of alpha and beta-NiMoO4 at a base pressure of similar to 1 x 10(-8) mbar. The obtained turn-on field at emission current density of 1 mu A/cm(2) for beta-NiMoO4 nanosheets and alpha-NiMoO4 is 1.3V/mu m and 2.2V/mu m respectively were observed. The maximum field emission current density of 1.006 mA/cm(2) at an applied electric field of 2.7V/mu m was achieved for beta-NiMoO4 nanosheets. Furthermore, we found that the beta-NiMoO4 nanosheets possess good field emission performance compared to alpha-NiMoO4. The results indicate that NiMoO4 can be used as a promising material in FE applications with possibility of tuning field emission performance by controlling the phase. (C) 2017 Elsevier B.V. All rights reserved.

PbS nanostar-like structures as field emitters - Pawar, Mahendra S.; Bankar, Prashant K.; More, Mahendra A.; Late, Dattatray J. (Chemistryselect, 2017)
The crystalline PbS nanostars were synthesized by thermal decomposition of thioacetamide (TAA) in aqueous solutions of lead acetate and acetic acid at 80 8 degrees C. The structure and morphology of the PbS nanostars have been characterized using X-Ray Diffraction (XRD), Raman Spectroscopy, Scanning Electron Microscopy (SEM) and Transmission Electron Microscopy (TEM). The optical properties of the PbS nanostars have been studied using UV-Visible absorption Spectroscopy (UVVis). The field emission investigations have been carried out on the as synthesized PbS nanostars at the base pressure of similar to 13 10(-8) mbar. The turn on field required to draw an emission current density of 1 mu A/cm(2) is found to be 1.8 V/mm. The emission current-time plots show good emission current stability of the PbS nanostar emitter over a period of 4 hrs. The results in terms of low turn-on field and long term emission current stability of the PbS nanostars emitter reveals that it can be used in field emission based vacuum microelectronics / nanoelectronic devices.

Graphene nanosheets assisted carbon hollow cylinder for high-performance field emission applications - Tripathi, Prashant; Gupta, Bipin Kumar; Bankar, Prashant K.; More, Mahendra A.; Late, Dattatray J.; Srivastava, Onkar Nath (Materials Research Express, 2019)
Electron sources are critical constituents for myriad many electronic applications including electron imaging, mass spectroscopy etc. Here, we report the realization of high-performance field emission from graphene assisted carbon hollow cylinders (Gr-CHCs) composed of multi-stacked radially aligned CNTs. These CHCs have built-in synthesis related Fe nanoparticles (NPs). This engineered nano-structure exhibits excellent field emission properties such as one of the ultra-low turn-on field (0.64V mu m(-1) at 10 mu A cm(-2)), low threshold field (0.74V mu m(-1) at 100 mu A cm(-2)), very high current density (15.49 mA cm(-2) at 1.32V mu m(-1)) which is nearly double the current density obtained in our previous study. High field enhancement factor (0.72. x. 10(4)) with highly stable emission current at 100 mu A was observed for more than 3 hrs at the base pressure of similar to 1. x. 10(-8) mbar. This study suggests an approach to enhance the current density using the proposed innovative nanostructure and forms the basic theme of this communication. Highly efficient and stable field emissions observed are attributed to the geometry of cylinder and the production of the high density of sharp protrusions within the graphene sheets which enhance the local electric field and dramatically enhance field emission. This innovative cylindrical geometry associated with graphene assisted on Fe bearing aligned CNTs along with the periphery of the bulk cylinder provides an easy injection of electrons from the conduction band of CHCs into the vacuum in the presence of an external electric field. The tunability of field emission properties of these CHCs can be easily achieved by tailoring their diameter (10 and 20 mm) and different concentrations of the precursor. This new approach of the graphene assisted cylindrical geometry-based field emitter source provides enormous prospects and demand for next-generation high resolutions display devices.
Keywords: Carbon nanotubes; field emission; graphene assisted carbon hollow cylinder; protrusions